Analysis of Giving DPT Immunization to Babies at Posyandu Lestari – Tangerang - Ella Nurlelawati; Ragil Supriyono; Partono Siswosuharjo (Akademi Keperawatan RSPAD Gatot Soebroto, 2023)
The purpose of this study was to identify the characteristics of mothers who gave DPT immunization to infants at Posyandu Lestari-Tangerang in 2015. Research Methodology This study was descriptive in nature by taking a sample taken from all populations, namely 51 respondents where the sample was taken using the Total Sampling method. Research results from the results of a study of 51 respondents on the characteristics of mothers based on the age of the majority were productive (20-35 years) namely 39 people (76.5%) and minorities of non-productive age (<20 years and> 35 years) namely 12 people ( 23.5 %), based on education the majority had higher education, namely 36 people (70.6 %) and a minority with low education, namely 15 people (29.0 %), based on parity the majority had parity 1-3, namely 32 people (62, 7%) and a minority with parity> 3, namely 19 people (37.3%), based on work the majority do not work, namely as many as 26 people (45.0%) and a minority work, namely as many as 25 people (49.0%). Conclusions based on the description of the material and discussion of the results of research on the characteristics of mothers regarding DPT immunization can be concluded as follows age, education, parity and occupation. Suggestions can be expected for health workers to be able to maintain and continue to improve the implementation of immunization.